Educational Policy Framework: Models, Theories and Processes (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
Policy education is the end result of decisions in the field of education taken by taking into account the educational components and related social components. To achieve high-quality education, teachers must understand the responsibilities of education, particularly those related to the length of time it takes to improve education. Because of this, the purpose of this article is to raise awareness of the importance of continuing education, the process of continuing education, the theory of continuing education, and the process of continuing education. This method of writing makes use of a research methodology. The writing of this article was carried out by studying national journals related to education policy. In order to improve education, several factors must be considered, including educational models, educational theory, and educational processes.